The alcohol abuse among college students: a literature review (Research, Society and Development, 2022)
Objective: analyze alcohol abuse among university students and describe the factors related to this consumption through a qualitative literature review. Methodology: this is systematic bibliographical review of the literature, based on the selected articles, their results were analyzed and discussed, and a review of the content addresses was presented. Following the inclusion criteria: in Portuguese, with the main subject Alcohol Use Among University Students, between the period from 2020 to 2022. For the exclusion criteria are: monographs, Course Conclusion Papers and literature review. From this, 14 articles were selected from the Google Scholar and ScieELO databases. Results: the present study observed a relationship between factors associated with alcohol consumption and university students. These factors are behavioral, socioeconomic, Family relationships that lead to stress, peer pressure, little contact with the Family, living away from the Family and risk behaviors.